Higher homocysteine and fibrinogen are associated with early-onset post-stroke depression in patients with acute ischemic stroke - Deng, Mingzhu; Zhou, Nina; Song, Kangping; Wang, Zhen; Zhao, Wei; Guo, Jiayu; Chen, Sufen; Tong, Yangping; Xu, Wei; Li, Fangyi (Frontiers in Psychiatry, 2024)
Background: Post-stroke depression (PSD) is a well-established psychiatric complication following stroke. Nevertheless, the relationship between early-onset PSD and homocysteine (Hcy) or fibrinogen remains uncertain.Methods: Acute ischemic stroke (AIS) patients who met the established criteria were enrolled in this study. Early-onset PSD was diagnosed two weeks after the stroke. The severity of depressive symptoms was assessed by the Hamilton Depression Scale-17 items (HAMD-17), with patients scored ≥7 assigned to the early-onset PSD group.Spearman rank correlation analysis was employed to evaluate the associations between Hcy, fibrinogen, and HAMD scores across all patients. Logistic regression analysis was conducted to investigate the relationship between Hcy, fibrinogen, and early-onset PSD.Receiver operating characteristic curve (ROC) analysis was also performed to detect the predictive ability of Hcy and fibrinogen for early-onset PSD.Results: Among the 380 recruited patients, a total of 106 (27.89%) patients were diagnosed with early-onset PSD. The univariate analysis suggested that patients in the PSD group had a higher admission National Institutes of Health Stroke Scale (NIHSS) score, modified Rankin Scale score (mRS), Hcy, and fibrinogen levels than patients in the non-PSD group (P<0.05). The logistic regression model indicated that Hcy (odds ratio[OR], 1.344; 95% confidence interval [CI] 1.209-1.494, P<0.001) and fibrinogen (OR, 1.576; P<0.001) were independently related to early-onset PSD.Area under curve (AUC) of Hcy, fibrinogen, and Hcy combined fibrinogen to predict early-onset PSD was 0.754, 0.698, and 0.803, respectively.This study indicates that Hcy and fibrinogen may be independent risk factors for early-onset PSD and can be used as predictive indicators for early-onset PSD.